INTERNATIONAL STRATEGIC MANAGEMENT (STUDY IN THE UNITED STATES OF AMERICA) - Maisyura; Rico Nur Ilham; Lidya Beru Tarigan; Eka Astria; Etia Farianti (RADJA PUBLIKA, 2023)
International strategic management is a comprehensive and ongoing process of management planning aimed at developing and implementing strategies that enable businesses to compete effectively in an international environment. The process of developing an international strategy is of course often referred to as